A Severe Case of Cutaneous Adverse Drug Reaction Secondary to a Novice Drug: Idelalisib - Gabriel, Joseph Gabriel (J Investig Med High Impact Case Rep, 2017)
Phosphatidylinositol 3-kinase δ (PIK3δ) is a tyrosine kinase essential for B cell survival, making it an important target in the treatment of chronic lymphocytic leukemia. Idelalisib is an inhibitor of PIK3δ demonstrating initial success in disease response, but is now shown to have a decreased overall survival and life-threatening serious adverse events. The following is an unfortunate case of a grade III adverse skin reaction secondary to idelalisib with the likely complication of methicillin-resistant Staphylococcus aureus bacteremia.